Technology-Based Learning Management in Senior High Schools - Gita Puspita; Yayat Hidayat (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
This study examines the management of technology-based learning at Madrasah Aliyah YPK Cijulang, which is a response to the developments of the digital era in education. Technology-based learning management is essential for creating an effective and relevant learning environment. This research employs a qualitative method with a case study approach, where data is collected through in-depth interviews with the head of the madrasah, teachers, and students, as well as direct observations and analysis of related documents. The aim of this study is to analyze the planning of technology-based learning management and to evaluate the implementation of digital learning management at Madrasah Aliyah YPK Cijulang. The results indicate that the learning planning at Madrasah Aliyah YPK Cijulang has involved the development of a curriculum integrated with technology in accordance with curriculum needs. The implementation of learning utilizes digital platforms such as the Pilar Sekolah application, PhET, and educational videos. However, this study also identifies challenges, such as the lack of technological skills among some teachers and internet access issues for students. The conclusion of this research emphasizes the importance of ongoing training for teachers and the development of adequate infrastructure to support the effective and efficient integration of technology in learning.